Analysis of Latrine Conditions, Clean Water Facilities, and Personal Hygiene on Diarrhea Incidence in Children Aged 24–59 Months - MuntheSeri Asnawati; Septiani, Misi; Manurung, Jasmen; SinagaLia Rosa Veronika (Window of Health : Jurnal Kesehatan, 2026)
Diarrheal disease remains a critical public health concern in Indonesia, particularly among children under five, where it ranks as a leading cause of morbidity. This study investigates the persistently high diarrhea prevalence among children aged 24–59 months in Paluh Sibaji Village, Pantai Labu District. Indonesia’s SKI 2023 reported a national prevalence of 7.4% in under-fives, peaking at 11.5% among the 1–4 age group. Focusing on this coastal community, the study uniquely examines the combined influence of environmental conditions and personal hygiene behaviors. Data were collected from 70 children aged 24–59 months and their mothers, randomly selected from 232 households. The researcher wanted to see if things like the condition of their toilets, access to clean water, and their hygiene practices were linked to whether or not the children had diarrhea. The result showed that over 30% of the children had experienced diarrhea. The analysis revealed strong associations between the condition of toilets, access to clean water, personal hygiene, and the occurrence of diarrhea. While the numbers suggest a strong link, other factors the researcher did not measure or potential biases in how the data were collected could be influencing these results. Personal hygiene seemed to have the strongest connection to diarrhea. In conclusion, the study emphasizes that a combination of sanitation issues and hygiene habits is significantly linked to diarrhea in this coastal community. Future studies that follow children over time could help us better understand the causes of diarrhea and rule out other contributing factors.